Framing Perceived Emotional Abuse by Former Intercollegiate Student-Athletes into Categories Based on Power - Alexander, Katherine N. (Victims & offenders, 2024)
Although contemporary researchers suggest that abuse is especially prevalent in sport, athletes’ experiences of coaches’ emotional abuse are not well understood. To address this gap, the present study was designed to examine how former intercollegiate student-athletes described experiences of emotional abuse in the coach-athlete relationship. Twenty former student-athletes were interviewed, and an inductive comparative analysis was utilized to interpret and situate the data. Results were framed in terms of power and were organized into four distinctive categories. Results highlight a critical need for institutions to reflect on current policies and practices regarding the prevention and investigation of athlete abuse.